Delinking : towards a polycentric world - Amin, Samir; Walfers, Michael (London : Zed Books, 1990)
Translation of: La decamexion pour sortir de systeme mondial
Keywords: Capitalism; Developing countries -- Dependency in foreign countries; Income distribution; International economic relations; Socialism